Variation in the Response of Clozapine Biotransformation Pathways in Human Hepatic Microsomes to CYP1A2‐ and CYP3A4‐selective Inhibitors. Issue 4 (15th December 2017) - Murray, Michael; Zhang, Wei V.; Edwards, Robert J.
Abstract: The atypical antipsychotic agent clozapine (CLZ) is effective in many patients who are resistant to conventional antipsychotic drugs. Cytochromes P450 (CYPs) 1A2 and 3A4 oxidize CLZ to norCLZ and CLZ N ‐oxide in human liver. Concurrent treatment with inducers and inhibitors of CYP1A2 modulates CLZ elimination that disrupts therapy. Drug–drug interactions involving CYP3A4 are also significant but less predictable. To further characterize the factors underlying these interactions, we used samples from a cohort of human livers to assess variation in CLZ oxidation pathways in relation to intrinsic CYP3A4 and CYP1A2 activities and the effects of the corresponding selective inhibitors ketoconazole (0.2 and 2 μM) and fluvoxamine (1 and 10 μM). The CYP3A4‐selective inhibitor ketoconazole (2 μM) impaired CLZ N ‐oxide formation in all 14 of the livers used in inhibition studies (≥50% inhibition) while the CYP1A2‐selective inhibitor fluvoxamine (10 μM) decreased norCLZ formation in nine. Ketoconazole effectively inhibited CLZ metabolism in five of seven livers that catalysed CYP3A4‐dependent testosterone 6β‐hydroxylation at or above the median rate and in four other livers with lower intrinsic CYP3A4 activity. Similarly, fluvoxamine (10 μM) readily inhibited CLZ oxidation in seven livers with high CYP1A2‐mediated 7‐ethoxyresorufin O ‐deethylation activity (at or above the median) and three livers with lower intrinsic CYP1A2 activity. In three livers, CLZ biotransformation was impaired by both ketoconazole and fluvoxamine, consistent with a major role for both CYPs. These findings suggest that the intrinsic activities of CYPs 1A2 and 3A4 are unrelated to the response to CYP‐selective inhibitors and that assessment of the activities in vivo may not assist the prediction of drug–drug interactions.